Effect of baclofen on gastric acid pocket in subjects with gastroesophageal reflux disease symptoms. Issue 8 (6th November 2015) - Scarpellini, E.; Boecxstaens, V.; Broers, C.; Vos, R.; Pauwels, A.; Tack, J
Summary: Postprandial gastroesophageal reflux (PGER) in the distal esophagus (DE) is associated with a gastric juice 'acid pocket' (AP). Baclofen reduces AP extension into the DE in healthy volunteers, in part through increased lower esophageal sphincter (LES) pressure. We aimed to verify whether baclofen also affects postprandial AP location and extent in gastroesophageal reflux disease (GERD) patients. Thirteen treatment‐naive heartburn‐prevalent GERD patients underwent two AP studies, after pretreatment with baclofen 40 mg or placebo 30 minutes preprandially. We performed pH‐probe stepwise pull‐throughs (PT) (1 cm/min, LES −10 to +5 cm) before and every 30 minutes from 30 minutes before up to 150 minutes after a test meal. After the meal, both after placebo and baclofen, gastric pH significantly dropped at 30, 60, 90 minutes postprandially (P: nadir pHs of 3.9 ± 0.6, 2.3 ± 0.6, 2.1 ± 0.4; B: nadir pHs of 2.5 ± 0.4, 2.8 ± 0.4, 2.5 ± 0.3; all P < 0.05). After placebo, LES pressure decreased at 60, 90 and 120 minutes postprandially (32.7 ± 6.1 vs. 24.5 ± 3.1, 27.3 ± 5.9, 27.3 ± 6.0 mmHg; analysis of variance [ANOVA], P = 0.037), but this was prevented by baclofen (25.4 ± 3.4 vs. 29.4 ± 2, 32.2 ± 1.4, 35.5 ± 1.7 mmHg, ANOVA, P = not significant (NS)). Baclofen did not significantly decrease the postprandial AP extent above the LES but prevented the postprandial increase in transient lower esophageal sphincter relaxations (TLESRs) (preprandial vs. postprandial, placebo: 1.1 ± 0.3 vs. 3.7 ± 0.7, P < 0.05; baclofen: 1.4 ± 0.4 vs. 2 ± 0.5, P = NS). In GERD patients, baclofen significantly increases postprandial LES pressure, prevents the increase TLESRs but, unlike in healthy volunteers, does not affect AP extension into the DE.